Harmonisasi Prinsip ‘Right to be Forgotten’ Pada Jadwal Retensi Arsip (JRA): Sebuah Analisis Komprehensif - Fachmi, Achmad; Inamullah, M. Hanif (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
This study aims to explore the differences in perspective between the Right to be Forgotten (RtbF) principle and the records management principles contained in the Records Retention Schedule (JRA). The focus of research is on efforts to harmonize the RtbF principle in Law No. 27 of 2022 on Personal Data Protection (PDP Law) and the JRA to ensure that personal record management complies with the new privacy regulations. The PDP Law recognizes the RtbF principle allowing individuals to request the deletion of their personal information. This principle significantly impacts the concept of privacy in record management but is potentially contradictory to the record management principles outlined in the JRA due to differing views on the retention period of personal records. This study employs an argumentative literature review method based on an interdisciplinary approach. The data analysis process begins with the selection of literature, followed by comprehensive reading and evaluation of selected literature from an inclusive perspective according to the research theme, and then summarizing, analyzing in depth, and critically synthesizing. The findings of this study indicate the need for harmonization in the implementation of the RtbF principle in the drafting of the JRA requiring consideration of user consent, privacy policy, and the categorization and classification levels of RtbF. Therefore, the development of JRA policies requires harmonization with the RtbF principle to accommodate both principles without violating each other, avoiding legal disputes, and breaching existing policies. Thus, a comprehensive examination of the RtbF principle and its relevance to archival science is necessary to support legal certainty in record management activities.